ANALISIS FAKTOR-FAKTOR YANG MEPENGARUHI EQUITY RISK PREMIUM - Rona Nabila Gusrima; Einde Evana; Yunia Amelia; Lindrianasari (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study has the aim of empirically testing the factors that affect the equity risk premium in companies listed on the IDX. This study uses sample data from 34 property and real estate companies listed on the Indonesia Stock Exchange with an observation period of 6 years from 2015-2020 taken using the purposive sampling method. The variables used in this study are audit tenure, book to market equity ratio, firm size, leverage, and earnings per share. The analysis technique used in this study is multiple linear regression, which is to determine the effect of audit period, book to market equity ratio, firm size, leverage, and earnings per share on the equity risk premium. The results showed that statistically the independent variable of tenure audit had a positive effect and the book to market equity ratio had a negative effect on the equity risk premium. while firm size, leverage, and earnings per share variables have no effect on the equity risk premium.